Scaling Up 3D-Printed Porous Reactors for the Continuous Synthesis of 2,5-Diformylfuran - Koufou, Dionysia; Kuhn, Simon (ACS Engineering Au, 2024)
The present study investigates the potential for scaling up 3D-printed porous reactors at the millimeter scale by integrating different reactor configurations in series. These reactor configurations, ranging from a single reactor (N = 1) to six reactors in series (N = 6), were evaluated for their performance in terms of axial dispersion in a gas–liquid system, with a focus on identifying potential dead zones. The scaled-up reactor systems exhibited a reduced deviation from plug flow behavior, mainly attributed to improved radial mixing maintained throughout the entire length of the porous structures. Among the various configurations tested, the scaled-up system featuring six reactors displayed the highest coefficient of variation (CoV) at approximately 24% for residence times exceeding 100 s. In all cases, the presence of stagnant zones influenced the shape of the residence time distribution (RTD) curves, although in the scaled-up system these stagnant zones did not significantly impact the overall performance or the yield of 2,5-diformylfuran (DFF). This was due to the narrow RTD and effective mass transfer between the stagnant and active flow compartments. Notably, the selectivity remained at 100%, and the highest yield of DFF (approximately 81%) was achieved for a residence time of 6.61 min in the scaled-up system. Despite introducing mass transfer limitations when operating at the millimeter scale, the scaled-up system achieved DFF productivity levels comparable to microreaction systems at significantly lower energy dissipation.